Film forming composition

JP7630937B2Active Publication Date: 2025-02-18KAO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020133920
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-07
Filing Date
2020-08-06
Publication Date
2025-02-18
Estimated Expiration
2040-08-06

Smart Images

  • Figure 0007630937000006
    Figure 0007630937000006
  • Figure 0007630937000007
    Figure 0007630937000007
  • Figure 0007630937000001
    Figure 0007630937000001
Patent Text Reader

Abstract

To provide a composition that is used for forming a coating directly on the skin by electrostatic spray, and that is capable of forming a coating that provides excellent compatibility with the skin, excellent adhesion, excellent followability to movement of the skin, and excellent resistance to moisture.SOLUTION: This composition comprises components (a), (b), and (c), and is used to form, directly on the skin by electrostatic spray, a coating that is formed of fibers and that has an elastic modulus of 1×104 N / m2 or more to 9×106 N / m2 or less. (a) A polymer having the ability to form a coating. (b) One or more volatile substances selected from alcohols and ketones. (c) 2 mass% or more to 30 mass% or less of a non-volatile oil having a logS value of -7 or more to less than zero.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for forming a coating directly on the skin by electrostatic spraying. [Background technology]

[0002] Various methods for forming a coating by electrostatic spraying are known. For example, Patent Document 1 describes a method for treating skin, which includes electrostatically spraying a composition onto the skin. The composition used in this method contains a liquid insulating material, a conductive material, a particulate powder material, and a thickener. Typically, this composition is a cosmetic or skin care composition containing a pigment. Specifically, a cosmetic foundation is used as the composition. That is, the invention described in Patent Document 1 is mainly intended to electrostatically spray a cosmetic foundation to make up the skin for beauty purposes.

[0003] US Patent No. 5,399,633 describes a disposable cartridge for use in an electrostatic cosmetic spray device. The electrostatic spray device is hand-held and self-contained. Like US Patent No. 5,399,633, the electrostatic spray device is used to spray cosmetic foundation. Furthermore, Patent Document 3 describes a method for improving the adhesion of a coating by applying a liquid to the skin before or after forming a coating on the surface of the skin by electrostatic spraying. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-104211 A [Patent Document 2] Special Publication No. 2003-507165 [Patent Document 3] JP 2017-78062 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when a coating is formed on the skin by electrostatic spraying according to the methods described in Patent Documents 1 and 2, the adhesion between the skin and the coating formed by electrostatic spray is insufficient, and the coating may be damaged or peeled off due to skin movement or moisture. Furthermore, when a coating is formed on the skin by the method described in Patent Document 3, the adhesion of the coating is improved to a certain extent, but there is a demand for the coating to have better ability to follow skin movement and durability against moisture, and there is also a demand for the coating to blend well with the skin and have a good feel when electrostatically sprayed on skin to which a cosmetic has been applied in advance. Therefore, an object of the present invention is to provide a composition for forming a coating directly on the skin by electrostatic spraying, which composition provides a coating that is excellent in compatibility with the skin, adhesion, ability to follow the movement of the skin, and durability against moisture. [Means for solving the problem]

[0006] Therefore, the present inventors conducted extensive research into the composition of an electrostatic spray composition used to form a film on the skin, rather than a composition to be applied before or after formation of a film on the skin by electrostatic spraying. As a result, they found that by using a non-volatile oil having a specific logS value in addition to a polymer and a volatile substance capable of forming a film, the film formed directly on the skin by electrostatic spray has a good elastic modulus and is excellent in compatibility with the skin, adhesion, ability to follow the movement of the skin, and durability against moisture, and thus completed the present invention.

[0007] That is, the present invention provides a coating composition comprising the following components (a), (b), and (c), and having an elastic modulus of 1×10 4 N / m 2 More than 9×10 6 N / m 2 The present invention relates to a film-forming composition for forming a fiber-based film directly on the skin by electrostatic spraying, which is as follows: (a) a polymer having a film-forming ability; (b) one or more volatile substances selected from alcohols and ketones; (c) Non-volatile oil with logS of -7 or more and less than 0, 2% by mass or more and 30% by mass or less Effect of the Invention

[0008] When a coating made of fibers is formed directly on the skin by electrostatic spraying using the composition of the present invention, the resulting coating has a good elastic modulus and is excellent in compatibility with the skin, adhesion, ability to follow the movement of the skin, and durability against moisture. In addition, when electrostatic spraying is performed on skin to which a cosmetic has already been applied, or when a coating is formed on the skin by electrostatic spraying and then a cosmetic is applied, the coating is extremely compatible with the skin. In addition, the elastic modulus of the coating obtained using the composition of the present invention is 1×10 7 N / m 2 Below, especially 1×10 4 N / m 2 More than 9×10 6 N / m 2 The following conditions are preferable in terms of the adhesion of the coating and its ability to follow the movement of the skin. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing the configuration of an electrostatic spray device preferably used in the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing how an electrostatic spray method is performed using an electrostatic spray device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The film-forming composition of the present invention is a composition for forming a film made of fibers directly on the skin by electrostatic spraying, and contains the above-mentioned components (a), (b) and (c). In the present invention, the film made of fibers means a film containing fibers made of component (a), and may be a film in which a liquid material is present other than the fibers, for example, around the fibers. In addition, the electrostatic spraying is preferably electrospinning.

[0011] The film-forming polymer of component (a) is generally a material that can dissolve in the volatile material of component (b). Here, dissolving means that when components (a) and (b) are mixed, component (a) is dispersed in component (b) at 20°C, and the dispersed state is visually uniform, preferably visually transparent or semi-transparent. The film-forming ability in the present invention is preferably a fiber-forming ability.

[0012] As the polymer having a film-forming ability, a suitable one is used depending on the properties of the volatile substance of component (b). Specifically, polymers having a film-forming ability are broadly classified into water-soluble polymers and water-insoluble polymers. In this specification, the term "water-soluble polymer" refers to a polymer that has the property that, after weighing 1 g of the polymer and immersing it in 10 g of ion-exchanged water in an environment of 1 atmosphere and 23°C, 0.5 g or more of the immersed polymer dissolves in water after 24 hours. On the other hand, in this specification, the term "water-insoluble polymer" refers to a polymer that has the property that, after weighing 1 g of the polymer and immersing it in 10 g of ion-exchanged water in an environment of 1 atmosphere and 23°C, less than 0.5 g of the immersed polymer dissolves in water after 24 hours.

[0013] Examples of water-soluble polymers capable of forming a coating include mucopolysaccharides such as pullulan, hyaluronic acid, chondroitin sulfate, poly-γ-glutamic acid, modified corn starch, β-glucan, glucooligosaccharide, heparin, and keratosulfate; natural polymers such as cellulose, pectin, xylan, lignin, glucomannan, galacturonic acid, psyllium seed gum, tamarind seed gum, gum arabic, tragacanth gum, soybean water-soluble polysaccharides, alginic acid, carrageenan, laminaran, agar (agarose), fucoidan, methylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose; and synthetic polymers such as partially saponified polyvinyl alcohol (when not used in combination with a crosslinking agent), low-saponified polyvinyl alcohol, polyvinylpyrrolidone (PVP), polyethylene oxide, and sodium polyacrylate. These water-soluble polymers can be used alone or in combination of two or more. Among these water-soluble polymers, from the viewpoint of easy production of the coating, it is preferable to use synthetic polymers such as pullulan, partially saponified polyvinyl alcohol, low saponified polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene oxide. When polyethylene oxide is used as the water-soluble polymer, its number average molecular weight is preferably 50,000 or more and 3,000,000 or less, more preferably 100,000 or more and 2,500,000 or less.

[0014] On the other hand, examples of polymers capable of forming a water-insoluble film include fully saponified polyvinyl alcohol, which can be insolubilized after film formation, partially saponified polyvinyl alcohol, which can be crosslinked after film formation by using a crosslinking agent in combination, oxazoline-modified silicones such as poly(N-propanoylethyleneimine) graft-dimethylsiloxane / γ-aminopropylmethylsiloxane copolymers, polyvinyl acetal diethylaminoacetate, zein (the main component of corn protein), polyester, polylactic acid (PLA), acrylic resins such as polyacrylonitrile resins and polymethacrylic acid resins, polystyrene resins, polyvinyl butyral resins, alkyl acetalized polyvinyl alcohols, polyethylene terephthalate resins, polybutylene terephthalate resins, polyurethane resins, polyamide resins, polyimide resins, polyamideimide resins, etc. These water-insoluble polymers can be used alone or in combination of two or more. Of these water-insoluble polymers, it is preferable to use fully saponified polyvinyl alcohol, which can be insolubilized after film formation, partially saponified polyvinyl alcohol, which can be crosslinked after film formation by using a crosslinking agent in combination, polyvinyl butyral resin, alkyl acetalized polyvinyl alcohol, polyurethane resin, oxazoline-modified silicone such as poly(N-propanoylethyleneimine) graft-dimethylsiloxane / γ-aminopropylmethylsiloxane copolymer, polyvinyl acetal diethylaminoacetate, zein, etc.

[0015] As component (a), a water-insoluble polymer capable of forming a coating is preferred, and one or more selected from the group consisting of partially saponified polyvinyl alcohol, low-saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, polyvinyl butyral resin, alkyl acetalized polyvinyl alcohol, polyurethane resin, polymethacrylic acid resin, oxazoline-modified silicone, polyvinyl acetal diethylamino acetate, and polylactic acid are more preferred.

[0016] The content of component (a) in the composition for forming a coating of the present invention is preferably 4% by mass or more, more preferably 5% by mass or more, even more preferably 6% by mass or more, and even more preferably 8% by mass or more. It is also preferably 35% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, and even more preferably 20% by mass or less. The content of component (a) in the composition for forming a coating is preferably 4% by mass or more and 35% by mass or less, more preferably 4% by mass or more and 30% by mass or less, even more preferably 6% by mass or more and 25% by mass or less, and even more preferably 8% by mass or more and 20% by mass or less. By including component (a) in the composition for forming a coating at this ratio, the desired coating can be efficiently formed, and the coating formed of fibers can be stably formed.

[0017] The volatile substance of component (b) is a substance that is volatile in a liquid state. In the composition for forming a film, component (b) is discharged from the tip of a nozzle toward the skin after the composition for forming a film placed in an electric field is sufficiently charged, and as component (b) evaporates, the charge density of the composition for forming a film becomes excessive, and component (b) further evaporates while being finely divided by Coulomb repulsion, and is blended for the purpose of finally forming a dry film. For this purpose, the vapor pressure of the volatile substance at 20°C is preferably 0.01 kPa or more and 106.66 kPa or less, more preferably 0.13 kPa or more and 66.66 kPa or less, even more preferably 0.67 kPa or more and 40.00 kPa or less, even more preferably 1.33 kPa or more and 40.00 kPa or less, and even more preferably 2.40 kPa or more and 40.00 kPa or less.

[0018] Among the volatile substances of component (b), the alcohols are preferably, for example, monohydric chain aliphatic alcohols, monohydric cyclic aliphatic alcohols, and monohydric aromatic alcohols. The monohydric chain aliphatic alcohols include linear or branched alcohols having 1 to 6 carbon atoms, the monohydric cyclic aliphatic alcohols include cyclic aliphatic alcohols having 4 to 6 carbon atoms, and the monohydric aromatic alcohols include benzyl alcohol and phenylethyl alcohol. Specific examples of these include methanol, ethanol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, 2-butyl alcohol, isobutyl alcohol, 2-methyl-2-propyl alcohol, n-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butyl alcohol, 2-methyl-2-butyl alcohol, 3-methyl-1-butyl alcohol, 3-methyl-2-butyl alcohol, neopentyl alcohol, n-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3 ... Examples of the alcohol include pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 3-methyl-2-pentanol, 4-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2,3-dimethyl-1-butanol, 3,3-dimethyl-1-butanol, 2,3-dimethyl-2-butanol, 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol, cyclobutanol, cyclopentanol, cyclohexanol, benzyl alcohol, and phenylethyl alcohol. These alcohols may be used alone or in combination of two or more selected from the above.

[0019] Among the volatile substances of component (b), the ketones include ketones having two alkyl groups having 1 to 4 carbon atoms, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc. These ketones can be used alone or in combination of two or more.

[0020] The volatile substance of component (b) may be one or a combination of two or more selected from the above alcohols and ketones, and may further contain water. The volatile substance of component (b) is more preferably one or more selected from ethanol, isopropyl alcohol, and n-butyl alcohol, even more preferably one or more selected from ethanol and isopropyl alcohol, and even more preferably ethanol. Furthermore, component (b) may further contain water in an amount of 0.4% by mass to 10% by mass.

[0021] From the viewpoint of fiber formability, the content of component (b) in the composition for forming a coating is preferably 45% by mass or more, more preferably 50% by mass or more, even more preferably 55% by mass or more, and even more preferably 60% by mass or more. Also, it is preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 90% by mass or less, and even more preferably 88% by mass or less. From the same viewpoint, the content of component (b) in the composition for forming a coating is preferably 45% by mass or more and 95% by mass or less, more preferably 50% by mass or more and 93% by mass or less, even more preferably 55% by mass or more and 90% by mass or less, and even more preferably 60% by mass or more and 88% by mass or less. By including component (b) in the composition for forming a coating at this ratio, the desired coating can be efficiently formed, and the coating formed of fibers can be stably formed. Furthermore, by including component (b) in the coating composition in this ratio, component (b) can be efficiently and sufficiently volatilized from the coating composition when the electrostatic spray method is performed.

[0022] Component (c), a non-volatile oil having a logS of -7 or more and less than 0, is a component that imparts flexibility and elasticity to the coating formed of fibers on the skin by electrostatic spraying, thereby improving the coating's adhesion to the skin, improving the coating's ability to follow the movement of the skin, and improving the coating's durability against moisture. Component (c) used in the present invention is a non-volatile oil and a component having a logS of -7 or more and less than 0.

[0023] Non-volatile means that when 1 g of oil is spread on a 48 mm diameter glass petri dish and left at 25°C and normal pressure for 24 hours, the mass loss is 1% or less.

[0024] LogS is an index of the solubility of a chemical in water, where "S" is the concentration of a saturated solution (mol / L). The logS values ​​in this invention were calculated using ChemDrawProfessional 17.1, using a calculation module based on Molecular Networks' cheminformatics platform MOSES. MOSES is developed, maintained, and owned by Molecular Networks GmbH (Erlangen, Germany). The log S of the component (c) is preferably −6 or more, more preferably −4 or more, and more preferably less than 0.

[0025] Component (c) is not particularly limited as long as it can be generally used in the field of cosmetics. For example, one or a combination of two or more non-volatile oils having a logS value of -7 or more and less than 0 selected from polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, ester oils, silicone oils, higher alcohols, higher fatty acids, nonionic surfactants, etc. can be used. As component (c), a non-volatile oil having a branched or unsaturated structure is preferred.

[0026] Examples of polyoxyalkylene glycols include polypropylene glycol, polybutylene glycol, polyoxypropylene glyceryl ether, polyoxybutylene glyceryl ether, polyoxyalkylene glyceryl ether (containing at least one alkylene oxide such as propylene oxide, butylene oxide, etc., as the constituent unit of oxyalkylene), and mixtures thereof. Here, as the polyoxyalkylene glycol, poly C3-C4 alkylene glycol is preferred, polypropylene glycol is more preferred, and those having an average molecular weight of 3000 or less are preferred, and those having an average molecular weight of 1000 or less are more preferred, among which PPG-7 (logS-0.9407), PPG-9 (logS-1.472), and PPG-17 (logS-3.596) are preferred, in order to improve the adhesion of the coating to the skin, improve the ability of the coating to follow the movement of the skin, and improve the durability of the coating against moisture by imparting flexibility and elasticity to the coating formed of fibers on the skin by electrostatic spray.

[0027] Examples of polyoxyalkylene alkyl ethers include polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, polyoxypropylene lauryl ether, polyoxypropylene oleyl ether, polyoxybutylene lauryl ether, polyoxybutylene oleyl ether, polyoxyalkylene alkyl ethers (alkyl ethers containing one or more alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide as oxyalkylene structural units and having a linear or branched alkyl group having about 1 to 20 carbon atoms), polyoxyethylene methyl glucoside, polyoxypropylene methyl glucoside, polyoxyethylene ... Examples of suitable fibrous coatings include polyoxyalkylene methylglucosides, polyoxyalkylene methylglucosides (containing one or more alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide as the constituent unit of oxyalkylene), and mixtures thereof. From the viewpoints of imparting flexibility and elasticity to the coating formed of fibers on the skin by electrostatic spraying, thereby improving the adhesion of the coating to the skin, improving the ability of the coating to follow the movement of the skin, and improving the durability of the coating against moisture, polyoxyethylene lauryl ether is preferred, and examples of such are laureth-3 (logS-3.377) and laureth-30 (logS-0.7034), with laureth-3 (logS-3.377) being preferred.

[0028] Examples of ester oils include diesters of sebacic acid such as diethyl sebacate, isononyl isononanoate (logS-4.995), isotridecyl isononanoate (logS-6.349), and other isononate esters, ethylhexanoic acid esters such as cetyl ethylhexanoate (logS-6.869), and other ethylhexanoic acid esters, glycol stearate (logS-4.8), glycol dilaurate (logS-7.0), di-2-ethylhexyl sebacate (logS-6.511), triethyl citrate (logS-0.5133), triethyl acetyl citrate (logS-1.402), tributyl acetyl citrate (logS-3.432), ultraviolet absorbers such as ethylhexyl methoxycinnamate (logS-4.894), and alkyl benzoates. Among these, di-2-ethylhexyl sebacate (logS-6.511), triethyl citrate (logS-0.5133), triethyl acetyl citrate (logS-1.402), tributyl acetyl citrate (logS-3.432), and ethylhexyl methoxycinnamate (logS-4.894) are preferred from the viewpoints of imparting flexibility and elasticity to the coating formed on the skin by electrostatic spray, thereby improving the coating's adhesion to the skin, improving the coating's ability to follow the movement of the skin, and improving the coating's durability against moisture.

[0029] Examples of silicone oils include chain silicones such as oxazoline-modified silicone, PEG-11 methyl ether dimethicone, PEG / PPG-20 / 22 butyl ether dimethicone, polyglyceryl-3 disiloxane dimethicone, polyglyceryl-3 disiloxane ethyl dimethicone, and lauryl polyglyceryl-3 disiloxane ethyl dimethicone.

[0030] Examples of higher alcohols include saturated linear monohydric alcohols and unsaturated monohydric alcohols. Examples of saturated linear monohydric alcohols include dodecanol (lauryl alcohol), tridodecanol, tetradodecanol (myristyl alcohol), pentadecanol, hexadecanol (cetyl alcohol), heptadecanol, octadecanol (stearyl alcohol), nonadecanol, icosanol (arachyl alcohol), henicosanol, docosanol (behenyl alcohol), tricosanol, tetracosanol (carnaubyl alcohol), pentacosanol, and hexacosanol (ceryl alcohol). Examples of unsaturated monohydric alcohols include oleyl alcohol and elaidyl alcohol.

[0031] Examples of higher fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid (logS-4.754), palmitoleic acid (logS-4.076), cis-6-hexadecenoic acid (logS-4.076), linoleic acid (logS-4.627), linolenic acid (logS-4.492), and ricinoleic acid (logS-3.883). Among these, electrostatic spraying imparts flexibility and elasticity to the fiber coating formed on the skin, improving the adhesion of the coating to the skin. In order to improve the ability of the coating to follow the movement of the skin and to improve the durability of the coating against moisture, unsaturated fatty acids having 16 to 24 carbon atoms are preferred, with oleic acid (logS-4.754), palmitoleic acid (logS-4.076), cis-6-hexadecenoic acid (logS-4.076), linoleic acid (logS-4.627), linolenic acid (logS-4.492) and ricinoleic acid (logS-3.883) being more preferred, and oleic acid (logS-4.754) being even more preferred.

[0032] Examples of nonionic surfactants include polyethylene glycol monofatty acid esters such as polyoxyethylene glycol monolaurate and polyoxyethylene glycol monostearate, polypropylene glycol monofatty acid esters such as polyoxypropylene glycol monolaurate and polyoxypropylene glycol monostearate, polybutylene glycol monofatty acid esters such as polyoxybutylene glycol monolaurate and polyoxybutylene glycol monostearate, polyoxyalkylene glycol monofatty acid esters (containing one or more alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide as the constituent unit of oxyalkylene) and mixtures thereof, polyoxyalkylene glycol difatty acid esters (containing one or more alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide as the constituent unit of oxyalkylene, and the two fatty acids may be the same or different fatty acids) and mixtures thereof, fatty acid polyoxyethylene sorbitan, maltitol hydroxy fatty alkyl ether. , alkylated polysaccharides, alkyl glucosides, sucrose fatty acid esters, polyoxyethylene hydrogenated castor oil glyceryl, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene-polyoxypropylene block copolymers, tetrapolyoxyethylene-tetrapolyoxypropylene-ethylenediamine condensates, polyoxyethylene-beeswax-lanolin derivatives, alkanolamides, polyoxyethylene-propylene glycol fatty acid esters, polyoxyethylene-alkylamines, polyoxyethylene-fatty acid amides, alkylethoxydimethylamine oxides, trioleyl phosphate, polyoxyethylene fatty acid glyceryl, isostearyl glyceryl ether, isodecyl glyceryl ether, 2-ethylhexyl glyceryl ether and other alkyl glyceryl ethers, among which fatty acid polyoxyethylene sorbitan is preferred from the viewpoint of imparting flexibility and elasticity to a coating formed of fibers on the skin by electrostatic spray, thereby improving the adhesion of the coating to the skin, improving the ability of the coating to follow the movement of the skin, and improving the durability of the coating against moisture,Polyoxyethylene (20) sorbitan monostearate (logS-2.883) is preferred.

[0033] Of these components (c), from the viewpoints of the adhesion of the coating to the skin, the ability of the coating to follow the movement of the skin, and the durability of the coating to moisture, one or more selected from poly C3-C4 alkylene glycol, polyoxyalkylene alkyl ether, ester oil, higher fatty acid, and nonionic surfactant are more preferred, and polyoxyalkylene alkyl ether, higher fatty acid, and nonionic surfactant are more preferred.

[0034] When the film-forming polymer of component (a) is a polyvinyl butyral resin or the like, the preferred component (c) is as follows: The non-volatile oil of component (c) is preferably a compound that easily interacts with the hydroxyl group, ester, and acetal moieties in the structure of the polyvinyl butyral resin, and specifically includes poly C3-C4 alkylene glycol, polyoxyalkylene alkyl ether, ester oil, silicone oil, nonionic surfactant, higher fatty acid, etc., but from the viewpoint of improving good elastic modulus, adhesion, ability to follow the movement of the skin, durability against moisture, and feel of the coating, it is preferable to include polypropylene glycol, ester oil, nonionic surfactant, polyoxyalkylene alkyl ether, and higher fatty acid, and more preferably polyoxyalkylene alkyl ether, higher fatty acid, and nonionic surfactant. One or more selected from these can be used in combination.

[0035] The content of component (c) in the composition for forming a coating film is preferably 0.1% by mass or more, preferably 0.5% by mass or more, preferably 1% by mass or more, preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 3.5% by mass or more, and even more preferably 4% by mass or more. Also, it is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, even more preferably 18% by mass or less, even more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 8% by mass or less. The content of component (c) in the composition for forming a coating film is preferably 2% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 25% by mass or less, even more preferably 3% by mass or more and 20% by mass or less, even more preferably 3% by mass or more and 18% by mass or less, even more preferably 3% by mass or more and 10% by mass or less, even more preferably 3.5% by mass or more and 10% by mass or less, and even more preferably 4% by mass or more and 8% by mass or less. When the content of component (c) is within this range, the coating formed of the fibers on the skin by electrostatic spraying is imparted with flexibility and good elasticity, the coating's adhesion to the skin and moisture resistance are improved, the coating's ability to follow the movement of the skin is improved, and the coating's compatibility with the skin is improved.

[0036] The mass ratio of component (a) to component (c) in the coating composition ((a) / (c)) is preferably 0.15 or more, more preferably 0.25 or more, even more preferably 0.5 or more, even more preferably 1 or more, and even more preferably 1.5 or more, from the viewpoints of flexibility, good elasticity, skin compatibility, adhesion, and durability to moisture of the coating formed from the fibers by electrostatic spraying. Also, it is preferably 300 or less, more preferably 50 or less, even more preferably 15 or less, even more preferably 13 or less, even more preferably 10 or less, even more preferably 8 or less, and even more preferably 6 or less. The (a) / (c) is preferably 0.15 or more and 300 or less, more preferably 0.25 or more and 50 or less, even more preferably 0.5 or more and 50 or less, even more preferably 0.5 or more and 15 or less, and even more preferably 1 or more and 15 or less. Moreover, it is preferably 1 or more and 13 or less, more preferably 1 or more and 10 or less, and further preferably 1.5 or more and 8 or less.

[0037] The mass ratio of component (b) to component (c) in the coating composition ((b) / (c)) is preferably 3 or more, more preferably 5 or more, even more preferably 7 or more, and even more preferably 9 or more, from the viewpoints of flexibility, good elasticity, skin compatibility, adhesion, and durability to moisture of the coating formed from the fibers by electrostatic spraying. Also, it is preferably 200 or less, more preferably 100 or less, even more preferably 50 or less, even more preferably 30 or less, and even more preferably 22 or less. The (b) / (c) is preferably 3 or more and 200 or less, more preferably 5 or more and 100 or less, even more preferably 7 or more and 50 or less, even more preferably 7 or more and 30 or less, and even more preferably 9 or more and 22 or less.

[0038] The mass ratio of component (a) to component (b) in the coating composition ((a) / (b)) is preferably 0.03 or more, more preferably 0.05 or more, even more preferably 0.1 or more, and even more preferably 0.12 or more, from the viewpoints of efficiently forming a desired coating, stably forming a coating made of fibers, and efficiently and sufficiently volatilizing component (b) from the coating composition when performing an electrostatic spray method. From the same viewpoints, it is preferably 0.6 or less, more preferably 0.45 or less, even more preferably 0.35 or less, even more preferably 0.3 or less, even more preferably 0.25 or less, even more preferably 0.2 or less, and even more preferably 0.18 or less. The (a) / (b) ratio is preferably 0.03 or more and 0.6 or less, more preferably 0.05 or more and 0.45 or less, even more preferably 0.1 or more and 0.35 or less, even more preferably 0.1 or more and 0.3 or less, and even more preferably 0.12 or more and 0.25 or less.

[0039] In addition to the above components, the coating composition may contain a conductivity control agent, an oil agent other than component (c), a color pigment, an extender pigment, a dye, a fragrance, a repellent, an antioxidant, a stabilizer, a preservative, various vitamins, water, etc. From the viewpoint of improving conductivity, the conductivity control agent is preferably an alkali metal salt or an ammonium salt, more preferably an ionic surfactant, and even more preferably one or more types selected from a cationic surfactant and an anionic surfactant.

[0040] The content of the conductivity control agent in the coating composition is not limited as long as it is an amount that causes the conductivity of the composition to fall within the above-mentioned range; from the viewpoint of stably forming a coating and preventing an excessive increase in conductivity, the content is preferably from 0.01% by mass to 10% by mass, more preferably from 0.05% by mass or more, even more preferably from 0.1% by mass or more, more preferably from 8% by mass or less, even more preferably from 6% by mass or less, even more preferably from 2.5% by mass or less, and even more preferably from 2% by mass or less.

[0041] From the viewpoints of stably forming a fiber film on the skin, spinnability during electrostatic spraying, drying of the fibers, thinning of the fibers, etc., the viscosity of the film-forming composition is preferably 2 mPa·s or more at 25°C, more preferably 5 mPa·s or more, even more preferably 10 mPa·s or more, even more preferably 30 mPa·s or more, still more preferably 50 mPa·s or more, and even more preferably 80 mPa·s or more. Also, it is preferably 3000 mPa·s or less, more preferably 2000 mPa·s or less, even more preferably 1500 mPa·s or less, even more preferably 1000 mPa·s or less, even more preferably 800 mPa·s or less, and even more preferably 500 mPa·s or less. The viscosity range of the composition for forming a coating is preferably 2 mPa·s to 3000 mPa·s, more preferably 5 mPa·s to 2000 mPa·s, even more preferably 10 mPa·s to 1500 mPa·s, even more preferably 30 mPa·s to 1000 mPa·s, even more preferably 50 mPa·s to 800 mPa·s, and even more preferably 80 mPa·s to 500 mPa·s. The viscosity of the composition for forming a coating is measured at 25°C using a B-type viscometer. For example, a B-type viscometer (TVB-10M) manufactured by Toki Sangyo Co., Ltd. can be used as the B-type viscometer. In this case, the measurement condition is a measurement temperature of 25°C. The measurement temperature at this time is the temperature of the composition for forming a coating. The type of rotor and the rotation speed of the rotor are selected according to the viscosity of the composition for forming a coating and the specifications of the measuring device to be used. For example, when using the B-type viscometer (TVB-10M) manufactured by Toki Sangyo Co., Ltd., the viscosity of the coating forming composition can be measured at 6 rpm using an M2 rotor if it is 2500 mPa·s or more, at 12 rpm using an M2 rotor if it is 1000 mPa·s or more but less than 2500 mPa·s, at 30 rpm using an M2 rotor if it is 500 mPa·s or more but less than 1000 mPa·s, at 60 rpm using an M2 rotor if it is 100 mPa·s or more but less than 500 mPa·s, and at 60 rpm using an M1 rotor if it is less than 100 mPa·s.In addition, the specifications for the B-type viscometer (TVB-10M) manufactured by Toki Sangyo Co., Ltd. also describe measurement conditions other than those described above, and the viscosity can also be measured under other measurement conditions depending on the viscosity of the coating-forming composition.

[0042] Next, a method for forming a fibrous coating directly on the skin by electrostatic spraying using the coating composition of the present invention will be described.

[0043] The film-forming composition is sprayed directly onto the site of human skin where a film is to be formed by electrostatic spraying. The electrostatic spraying method includes a step of electrostatically spraying the film-forming composition onto the skin using an electrostatic spraying device. The electrostatic spraying device basically includes a container for containing the composition, a nozzle for discharging the composition, a supply device for supplying the composition contained in the container to the nozzle, and a power source for applying a voltage to the nozzle.

[0044] FIG 1 shows a schematic diagram illustrating the configuration of an electrostatic spray device preferably used in the present invention. The electrostatic spray device 10 shown in the figure is equipped with a low-voltage power supply 11. The low-voltage power supply 11 is capable of generating a voltage of several volts to several tens of volts. For the purpose of increasing the portability of the electrostatic spray device 10, it is preferable that the low-voltage power supply 11 is made up of one or more batteries. Furthermore, using a battery as the low-voltage power supply 11 has the advantage that it can be easily replaced as necessary. An AC adapter or the like can also be used as the low-voltage power supply 11 instead of a battery.

[0045] The electrostatic spray device 10 also includes a high-voltage power supply 12. The high-voltage power supply 12 is connected to the low-voltage power supply 11, and includes an electric circuit (not shown) that boosts the voltage generated by the low-voltage power supply 11 to a high voltage. The boost electric circuit is generally composed of a transformer, a capacitor, semiconductor elements, etc.

[0046] The electrostatic spray device 10 further includes an auxiliary electric circuit 13. The auxiliary electric circuit 13 is interposed between the low-voltage power supply 11 and the high-voltage power supply 12 described above, and has a function of adjusting the voltage of the low-voltage power supply 11 to stably operate the high-voltage power supply 12. The auxiliary electric circuit 13 further has a function of controlling the rotation speed of a motor included in a micro gear pump 14 described below. By controlling the rotation speed of the motor, the amount of the composition for forming a film supplied from a container 15 for the composition for forming a film to the micro gear pump 14 is controlled. A switch SW is attached between the auxiliary electric circuit 13 and the low-voltage power supply 11, and the electrostatic spray device 10 can be operated / stopped by turning the switch SW on and off.

[0047] The electrostatic spray device 10 further includes a nozzle 16. The nozzle 16 is made of various conductive materials such as metals or non-conductive materials such as plastics, rubber, and ceramics, and has a shape that allows the coating composition to be discharged from its tip. A minute space through which the coating composition flows is formed in the nozzle 16 along the longitudinal direction of the nozzle 16. The size of the cross section of this minute space, expressed in diameter, is preferably 100 μm or more and 1000 μm or less. The nozzle 16 communicates with the micro gear pump 14 via a conduit 17. The conduit 17 may be conductive or non-conductive. The nozzle 16 is also electrically connected to the high voltage power supply 12. This allows a high voltage to be applied to the nozzle 16. In this case, in order to prevent an excessive current from flowing when the nozzle 16 is directly touched by a human body, the nozzle 16 and the high voltage power supply 12 are electrically connected to each other via a current limiting resistor 19.

[0048] The micro gear pump 14, which is in communication with the nozzle 16 via a pipe 17, functions as a supply device that supplies the coating composition contained in a container 15 to the nozzle 16. The micro gear pump 14 operates by receiving power from a low voltage power supply 11. The micro gear pump 14 is also configured to supply a predetermined amount of the coating composition to the nozzle 16 under the control of an auxiliary electric circuit 13.

[0049] A container 15 is connected to the micro gear pump 14 via a flexible pipe 18. The container 15 contains a coating composition. The container 15 is preferably in the form of a replaceable cartridge. Note that a piston pump may be used instead of the micro gear pump 14, and configured to supply a predetermined amount of the coating composition to the nozzle 16 under the control of an auxiliary electric circuit 13.

[0050] The electrostatic spray device 10 having the above configuration can be used, for example, as shown in FIG. 2. FIG. 2 shows a handheld electrostatic spray device 10 having a size that can be held in one hand. In the electrostatic spray device 10 shown in the figure, all of the components shown in the configuration diagram in FIG. 1 are housed in a cylindrical housing 20. A nozzle (not shown) is disposed at one end 10a in the longitudinal direction of the housing 20. The nozzle is disposed in the housing 20 so that the spray direction of the composition coincides with the vertical direction of the housing 20 and is convex toward the skin. By disposing the nozzle tip so that it is convex toward the skin in the vertical direction of the housing 20, the composition for forming a coating is less likely to adhere to the housing, and a coating can be stably formed.

[0051] When the electrostatic spray device 10 is operated, a user, i.e., a person who forms a coating on a part of the skin where a coating is to be formed by electrostatic spray, holds the device 10 in his / her hand and points one end 10a of the device 10, where a nozzle (not shown) is disposed, toward the application part where electrostatic spraying is to be performed. Fig. 2 shows a state in which one end 10a of the electrostatic spray device 10 is pointed toward the inside of the forearm of the user. In this state, the switch of the device 10 is turned on to perform the electrostatic spray method. When the device 10 is turned on, an electric field is generated between the nozzle and the skin. In the embodiment shown in FIG. 2, a positive high voltage is applied to the nozzle, and the skin becomes the negative electrode. When an electric field is generated between the nozzle and the skin, the film-forming composition at the tip of the nozzle is polarized by electrostatic induction, the tip becomes cone-shaped, and droplets of the charged film-forming composition are discharged from the tip of the cone into the air along the electric field toward the skin. When the solvent component (b) evaporates from the charged film-forming composition discharged into space, the charge density on the surface of the film-forming composition becomes excessive, and the film-forming composition progresses through the space while repeatedly being finely divided by Coulomb repulsion, and reaches the skin. In this case, by appropriately adjusting the viscosity of the film-forming composition, the volatile substance as the solvent is volatilized from the droplets while being discharged into space, and the component (b) having film-forming ability as a solute is discharged into the space. The polymer (a) can be solidified and stretched by a potential difference to form fibers, which can then be deposited on the application site. For example, increasing the viscosity of the film-forming composition makes it easier to deposit the composition in the form of fibers on the application site. This forms a porous film made of a deposit of fibers on the surface of the application site. Such a porous film made of a deposit of fibers can also be formed by adjusting the distance between the nozzle and the skin or the voltage applied to the nozzle.

[0052] During electrostatic spraying, a high potential difference occurs between the nozzle and the skin. However, since the impedance is very large, the current flowing through the human body is extremely small. The inventors have confirmed that the current flowing through the human body during electrostatic spraying is several orders of magnitude smaller than the current flowing through the human body due to static electricity generated in everyday life.

[0053] When the fiber deposit is formed by the electrostatic spray method, the thickness of the fiber, expressed in terms of a circle equivalent diameter, is preferably 50 nm or more, more preferably 100 nm or more, and even more preferably 200 nm or more, and is preferably 3000 nm or less, more preferably 1500 nm or less, and even more preferably 1000 nm or less. The fiber thickness can be measured, for example, by observing the fiber with a scanning electron microscope (SEM) at 10,000 times magnification, removing defects (fiber clumps, fiber intersections, and liquid droplets) from the two-dimensional image, randomly selecting 10 fibers, drawing a line perpendicular to the longitudinal direction of the fiber, and directly reading the fiber diameter. The fibers of the present invention are preferably continuous fibers, and preferably have a length of at least 100 times the thickness of the fibers. For example, the formed coating preferably contains fibers containing component (a) and having a length of preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more. In this specification, a fiber having a length of 100 times or more than the thickness of the fibers is defined as a "continuous fiber". The cross-sectional shape of the fiber is preferably circular or elliptical, and the thickness of the fiber is the diameter in the case of a circular shape, and the length of the major axis in the case of an elliptical shape. And, the coating produced by the electrostatic spray method is preferably a porous discontinuous coating consisting of a deposit of one or more continuous fibers.

[0054] According to the electrostatic spray method, the coating composition is sprayed while being electrically charged, and is susceptible to the effects of moisture in the air when the humidity is high. However, by including a conductivity control agent, the coating composition can be made less susceptible to this effect.

[0055] The method for producing the coating composition may involve stirring a mixed solution containing all of the components, but it is preferable to include step 1 in which mixed solution 1 containing components other than component (a) is stirred, followed by step 2 in which component (a) is added and stirred and mixed. These steps 1 and 2 are preferably carried out at room temperature of 10°C to 30°C.

[0056] The distance between the nozzle and the skin depends on the voltage applied to the nozzle, but is preferably 10 mm or more, more preferably 20 mm or more, and even more preferably 40 mm or more. It is also preferably 160 mm or less, more preferably 140 mm or less, and even more preferably 120 mm or less. By having the distance between the nozzle and the skin in this range, the formation of a coating can be improved. The distance between the nozzle and the skin can be measured by a commonly used non-contact sensor or the like.

[0057] Regardless of whether the coating applied by electrostatic spraying is porous or not, the coating shall have a basis weight of 0.10 g / m 2 It is preferable that the content is 1.0 g / m or more. 2 More preferably, it is 50 g / m or more. 2 It is preferable that the thickness is less than 40 g / m 2 The basis weight of the formed coating is preferably 0.10 g / m or less. 2 More than 50g / m 2 Preferably, the content is 1.0 g / m or less. 2 More than 40g / m 2 By setting the basis weight of the coating in this manner, it is possible to improve the compatibility and adhesion of the coating to the skin, the ability of the coating to conform to the skin, and the moisture durability of the coating.

[0058] The elastic modulus of the film formed on the skin using the film-forming composition of the present invention is 1×10 7 N / m 2 A value of 1×10 or less is preferable in terms of the adhesion of the coating and its ability to follow the movement of the skin. 4 N / m 2 More than 9×10 6 N / m 2 More preferably, it is 1×10 4 N / m 2 Below 8×10 6 N / m 2 More preferably, it is 1×10 4 N / m 2 More than 7×10 6 N / m 2More preferably, it is equal to or less than 1000 mm. This elastic modulus can be adjusted mainly by the type and content of the component (c). Here, the elastic modulus is a value measured at 25°C using a tensile tester. As the tensile tester, a Tensilon UTC-100W manufactured by Orientec Co., Ltd. can be used. A 7.5 cm x 2.5 cm hole is made in the center of a 10 cm x 10 cm aluminum foil (manufactured by AS ONE Co., Ltd.), and a coating is formed by electrostatically spraying for 1 minute over an area of ​​10 cm x 5 cm that completely includes the hole. After making a cut in the aluminum foil perpendicular to the short side (2.5 cm) of the hole, the foil is pulled in a direction parallel to the short side of the hole at a pulling speed of 500 mm / min to measure the stress-strain curve. The initial slope of the stress-strain curve was calculated, and the elastic modulus was calculated for a width of 7.5 cm and a length of 2.5 cm with the thickness set to a constant value of 20 μm.

[0059] In the present invention, a skin care cosmetic or makeup cosmetic may be applied to the skin before or after the electrostatic spraying step in which a coating is formed on the skin by electrostatic spraying using the above-mentioned coating-forming composition of the present invention. By electrostatically spraying before or after application of the cosmetic in this way, the cosmetic present on the skin can be covered with a coating, which significantly improves the compatibility of the cosmetic with the skin, improves durability against moisture, and allows the cosmetic to be stably held on the skin for a long period of time.

[0060] Examples of skin care cosmetics used here include lotions, milky lotions, creams, beauty serums (skin whitening, anti-wrinkle, etc.), all-in-one cosmetics, UV care cosmetics, BB creams, oils, oil gels, lotions, etc., and examples of makeup cosmetics include makeup bases, foundations, concealers, blushers, eye shadows, mascaras, eyeliners, eyebrow creams, overcoats, lipsticks, etc.

[0061] Furthermore, examples of means for applying the skin care cosmetic or the makeup cosmetic to the skin by means other than electrostatic spray include application with the fingers, application using nonwoven fabric such as cotton, application using a sponge, spraying with a normal spray, spraying with a mist, steam, dripping, sprinkling, and the like.

[0062] In relation to the above-mentioned embodiments, the present invention further discloses the following compositions and methods.

[0063] <1> The composition contains the following components (a), (b), and (c), and the elastic modulus of the film formed from the composition is 1×10 4 N / m 2 More than 9×10 6 N / m 2 A film-forming composition for forming a fiber-formed film directly on the skin by electrostatic spraying, which is: (a) a polymer having a film-forming ability; (b) one or more volatile substances selected from alcohols and ketones; (c) Non-volatile oil with logS of -7 or more and less than 0, 2% by mass or more and 30% by mass or less

[0064] <2> Component (a) is preferably one or more selected from water-insoluble polymers capable of forming a film. <1> The film-forming composition described above. <3> Component (a) is a water-insoluble polymer capable of forming a film, and is preferably a fully saponified polyvinyl alcohol which can be insolubilized after film formation, a partially saponified polyvinyl alcohol which can be crosslinked after film formation by using a crosslinking agent in combination, an oxazoline-modified silicone such as poly(N-propanoylethyleneimine) graft-dimethylsiloxane / γ-aminopropylmethylsiloxane copolymer, polyvinyl acetal diethylaminoacetate, zein (a major component of corn protein), polyester, polylactic acid (PLA), polyacrylonitrile resin, acrylic resin such as polymethacrylic acid resin, polystyrene resin, or polyvinyl butyral. The resin is one or more selected from the group consisting of resins, alkyl acetalized polyvinyl alcohols, polyethylene terephthalate resins, polybutylene terephthalate resins, polyurethane resins, polyamide resins, polyimide resins, and polyamideimide resins, and more preferably one or more selected from the group consisting of fully saponified polyvinyl alcohols which can be insolubilized after film formation, partially saponified polyvinyl alcohols which can be crosslinked after film formation by using a crosslinking agent in combination, polyvinyl butyral resins, alkyl acetalized polyvinyl alcohols, polyurethane resins, oxazoline-modified silicones, polyvinyl acetal diethylamino acetate, and zein. <1> or <2> The coating composition according to claim 1, <4> The content of component (a) is preferably 4% by mass or more, more preferably 5% by mass or more, even more preferably 6% by mass or more, even more preferably 8% by mass or more, and preferably 35% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less, even more preferably 20% by mass or less, preferably 4% by mass or more and 30% by mass or less, more preferably 4% by mass or more and 25% by mass or less, even more preferably 6% by mass or more and 25% by mass or less, and even more preferably 8% by mass or more and 20% by mass or less. <1> ~ <3> 2. The coating composition according to claim 1 , <5> The content of component (a) is 4% by mass or more and 30% by mass or less. <1> ~ <4> 2. The coating composition according to claim 1 , <6> The content of component (a) is 4% by mass or more and 25% by mass or less. <1> ~ <4> 2. The coating composition according to claim 1 , <7> The alcohol of component (b) is preferably one or more selected from monohydric chain aliphatic alcohols, monohydric cyclic aliphatic alcohols, and monohydric aromatic alcohols, more preferably one or more selected from monohydric chain aliphatic alcohols having a linear or branched chain with 1 to 6 carbon atoms, monohydric cyclic aliphatic alcohols having 4 to 6 carbon atoms, benzyl alcohol, and phenylethyl alcohol, and even more preferably one or more selected from ethanol, isopropyl alcohol, n-butyl alcohol, phenylethyl alcohol, n-propanol, and n-pentanol. <1> ~ <6> 2. The coating composition according to claim 1 , <8> The ketone of component (b) is preferably a ketone having two alkyl groups having 1 to 4 carbon atoms, and more preferably one or more selected from acetone, methyl ethyl ketone, and methyl isobutyl ketone. <1> ~ <7> 2. The coating composition according to claim 1 , <9> The component (b) is preferably one or more selected from ethanol, isopropyl alcohol, and n-butyl alcohol, more preferably one or more selected from ethanol and isopropyl alcohol, and even more preferably ethanol. The component (b) may further contain water. <1> ~ <8> 2. The coating composition according to claim 1 , <10> The content of component (b) is preferably 45% by mass or more, more preferably 50% by mass or more, even more preferably 55% by mass or more, even more preferably 60% by mass or more, and is preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 90% by mass or less, and even more preferably 88% by mass or less, and is preferably 45% by mass or more and 95% by mass or less, more preferably 50% by mass or more and 93% by mass or less, even more preferably 50% by mass or more and 90% by mass or less, and even more preferably 50% by mass or more and 88% by mass or less. <1> ~ <9> 2. The coating composition according to claim 1 , <11> The content of component (b) is 50% by mass or more and 95% by mass or less. <1> ~ <10> 2. The coating composition according to claim 1 , <12> The content of component (b) is 50% by mass or more and 93% by mass or less. <1> ~ <10> 2. The coating composition according to claim 1 , <13> Component (c) is preferably one or more non-volatile oils having a logS of -7 or more and less than 0 selected from polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, ester oils, silicone oils, higher alcohols, higher fatty acids, and nonionic surfactants, and more preferably one or more non-volatile oils having a logS of -7 or more and less than 0 selected from poly C3-C4 alkylene glycols, polyoxyalkylene alkyl ethers, ester oils, higher fatty acids, and nonionic surfactants. <1> ~ <12> 2. The coating composition according to claim 1 , <14> Component (c) is preferably a compound that easily interacts with hydroxyl groups, esters, and acetal moieties in the structure of the polybutyral resin, more preferably one or more selected from poly C3-C4 alkylene glycol, polyoxyalkylene alkyl ether, ester oil, silicone oil, nonionic surfactant, higher fatty acid, and ultraviolet absorber, and even more preferably one or more selected from polypropylene glycol, ester oil, nonionic surfactant, polyoxyalkylene alkyl ether, and higher fatty acid. <1> ~ <13> 2. The coating composition according to claim 1 , <15> The content of component (c) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 3.5% by mass or more, and even more preferably 4% by mass or more. It is also preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, even more preferably 18% by mass or less, even more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 8% by mass or less, and it is preferably 2% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 25% by mass or less, even more preferably 3% by mass or more and 20% by mass or less, even more preferably 3% by mass or more and 20% by mass or less, even more preferably 3% by mass or more and 18% by mass or less, even more preferably 3% by mass or more and 10% by mass or less, even more preferably 3.5% by mass or more and 10% by mass or less, and even more preferably 4% by mass or more and 8% by mass or less. <1> ~ <14> 2. The coating composition according to claim 1 , <16> The content of component (c) is 2% by mass or more and 25% by mass or less. <1> ~ <15> 2. The coating composition according to claim 1 , <17> The content of component (c) is 3% by mass or more and 20% by mass or less. <1> ~ <15> 2. The coating composition according to claim 1 , <18> The content mass ratio of component (a) to component (c) ((a) / (c)) is preferably 0.15 or more, more preferably 0.25 or more, even more preferably 0.5 or more, even more preferably 1 or more, even more preferably 1.5 or more, and is preferably 300 or less, more preferably 50 or less, even more preferably 15 or less, even more preferably 13 or less, even more preferably 10 or less, even more preferably 8 or less, even more preferably 6 or less, preferably 0.15 or more and 300 or less, more preferably 0.25 or more and 50 or less, even more preferably 0.5 or more and 50 or less, even more preferably 0.5 or more and 15 or less, preferably 1 or more and 13 or less, more preferably 1 or more and 10 or less, and even more preferably 1.5 or more and 8 or less. <1> ~ <17> 2. The coating composition according to claim 1 , <19> The mass ratio of component (a) to component (c) ((a) / (c)) is 0.15 or more and 300 or less. <1> ~ <18> 2. The coating composition according to claim 1 , <20> The mass ratio of component (a) to component (c) ((a) / (c)) is 0.25 or more and 50 or less. <1> ~ <19> 2. The coating composition according to claim 1 , <21> The content mass ratio of component (b) to component (c) ((b) / (c)) is preferably 3 or more, more preferably 5 or more, even more preferably 7 or more, and even more preferably 9 or more. It is also preferably 200 or less, more preferably 100 or less, even more preferably 50 or less, even more preferably 30 or less, even more preferably 22 or less, preferably 3 to 200, more preferably 5 to 100, even more preferably 7 to 50, even more preferably 7 to 30, and even more preferably 9 to 22. <1> ~ <20> 2. The coating composition according to claim 1 , <22> The mass ratio of component (b) to component (c) ((b) / (c)) is preferably 3 or more and 200 or less. <1> ~ <21> 2. The coating composition according to claim 1 , <23> The content mass ratio of component (a) to component (b) ((a) / (b)) is preferably 0.03 or more, more preferably 0.05 or more, even more preferably 0.1 or more, even more preferably 0.12 or more, and preferably 0.6 or less, more preferably 0.45 or less, even more preferably 0.35 or less, even more preferably 0.3 or less, even more preferably 0.25 or less, even more preferably 0.2 or less, even more preferably 0.18 or less, preferably 0.03 or more and 0.6 or less, more preferably 0.05 or more and 0.45 or less, even more preferably 0.1 or more and 0.35 or less, even more preferably 0.1 or more and 0.3 or less, and even more preferably 0.12 or more and 0.25 or less. <1> ~ <22> 2. The coating composition according to claim 1 , <24> The mass ratio of component (a) to component (b) ((a) / (b)) is 0.03 or more and 0.6 or less. <1> ~ <23> 2. The coating composition according to claim 1 , <25> The mass ratio of component (a) to component (b) ((a) / (b)) is 0.05 or more and 0.45 or less. <1> ~ <24> 2. The coating composition according to claim 1 , <26> Contains components selected from the group consisting of electrical conductivity control agents, oils other than component (c), color pigments, extender pigments, dyes, fragrances, repellents, antioxidants, stabilizers, preservatives, various vitamins, and water. <1> ~ <25> 2. The coating composition according to claim 1 , <27> The conductivity control agent is preferably a component that causes the conductivity of the coating composition to be 10 μS / cm or more and 300 μS / cm or less at 25° C. <26> The coating composition according to claim 1, <28> The conductivity control agent is preferably an alkali metal salt or an ammonium salt, more preferably an ionic surfactant, and further preferably one or more selected from a cationic surfactant and an anionic surfactant. <26> or <27> The coating composition according to claim 1, <29> The conductivity control agent is one or more selected from the group consisting of quaternary ammonium salts and acylamino acid salts. <26> ~ <28> 2. The coating composition according to claim 1 , <30> The content of the conductivity control agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, preferably 10% by mass or less, more preferably 8% by mass or less, even more preferably 6% by mass or less, even more preferably 2.5% by mass or less, even more preferably 2% by mass or less, preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 8% by mass or less, even more preferably 0.1% by mass or more and 6% by mass or less, even more preferably 0.1% by mass or more and 2.5% by mass or less, and even more preferably 0.1% by mass or more and 2% by mass or less. <26> ~ <29> 2. The coating composition according to claim 1 , <31> The viscosity of the coating composition at 25°C is preferably 2 mPa·s or more, more preferably 5 mPa·s or more, even more preferably 10 mPa·s or more, even more preferably 30 mPa·s or more, even more preferably 50 mPa·s or more, even more preferably 80 mPa·s or more, and is preferably 3000 mPa·s or less, more preferably 2000 mPa·s or less, even more preferably 1500 mPa·s or less, and even more preferably 1000 mPa·s or less; It is more preferably 800 mPa·s or less, even more preferably 500 mPa·s or less, and also preferably from 2 to 3000 mPa·s, more preferably from 5 to 2000 mPa·s, even more preferably from 10 to 1500 mPa·s, even more preferably from 30 to 1000 mPa·s, even more preferably from 50 to 800 mPa·s, and even more preferably from 80 to 500 mPa·s. <1> ~ <30> 2. The coating composition according to claim 1 , <32> The elastic modulus of the resulting coating is 1×10 4 N / m 2 8×10 or more 6 N / m 2 Preferably, it is less than or equal to 1×10 4 N / m 2 Below 7×10 6 N / m 2 More preferably: <1> ~ <31> 2. The coating composition according to claim 1 , <33> For use in combination with cosmetics that are applied to the skin by means other than electrostatic spray <1> ~ <32> 2. The coating composition according to claim 1 , <34> The cosmetic is preferably a skin care cosmetic or a makeup cosmetic. <33> The coating composition according to claim 1, <35> The composition contains the following components (a), (b), and (c), and the elastic modulus of the film formed from the composition is 1×10 4 N / m 2 More than 9×10 6 N / m 2A film-forming composition for forming a fiber-formed film directly on the skin by electrostatic spraying, which is: (a) a polymer capable of forming a film, the polymer comprising: 4% by mass or more and 35% by mass or less; (b) 45% by mass or more and 95% by mass or less of one or more volatile substances selected from alcohols and ketones; (c) Non-volatile oil with logS of -7 or more and less than 0, 2% by mass or more and 30% by mass or less <36> A method for producing a coating for forming a coating on a surface of an object to be coated, comprising an electrostatic spraying step of electrostatically spraying a composition directly onto the object to be coated to form a coating consisting of a deposit containing fibers, the composition comprising the following components (a), (b) and (c), and the coating formed from the composition has an elastic modulus of 1×10 4 N / m 2 More than 9×10 6 N / m 2 The method for producing a coating, (a) a polymer capable of forming a film, the polymer comprising: 4% by mass or more and 35% by mass or less; (b) 45% by mass or more and 95% by mass or less of one or more volatile substances selected from alcohols and ketones; (c) Non-volatile oil with logS of -7 or more and less than 0, 2% by mass or more and 30% by mass or less <37> The composition contains the following components (a), (b), and (c), and the elastic modulus of the film formed from the composition is 1×10 4 N / m 2 More than 9×10 6 N / m 2 A cosmetic product formed from a film-forming composition for forming a fiber-formed film directly on the skin by electrostatic spraying, the composition being as follows: (a) a polymer capable of forming a film, the polymer comprising: 4% by mass or more and 35% by mass or less; (b) 45% by mass or more and 95% by mass or less of one or more volatile substances selected from alcohols and ketones; (c) Non-volatile oil with logS of -7 or more and less than 0, 2% by mass or more and 30% by mass or less EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0066] [Test Example 1] [Examples 1 to 19, Comparative Examples 1 to 3] (1) Preparation of film-forming composition Polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.: product name: S-LEC B BM-1) was used as component (a) of the coating composition, and 99.5% ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) was used as component (b). Furthermore, the components shown in Tables 1 to 3 were used as component (c). The contents of each component shown in Tables 1 to 3 are effective amounts, and the units are mass %.

[0067] (2) Cosmetic application process Prior to the electrostatic spraying process, 200 mg of the cosmetic composition shown in Table 4 was applied to the outer part of a person's lower leg (5 x 5 cm) using a sponge. Approximately 50 mg of the cosmetic composition was applied to the skin.

[0068] (3) Electrostatic spray process Using an electrostatic spray device 10 having the configuration shown in Fig. 1 and the appearance shown in Fig. 2, the coating composition was applied by electrostatic spray to the area where the cosmetic was applied. That is, the coating composition was applied by electrostatic spray onto the skin where the cosmetic was applied, forming a coating made of fibers. Hand pressing was performed to blend the cosmetic and the coating. The coating composition was applied by electrostatic spray under the following conditions: -Applicable area: outer part of human lower limb (5 x 5 cm), (Area to which the skin care cosmetic is applied) Electrostatic spray application time: 30 seconds ·Discharge speed of film-forming composition: 0.1g / min Distance between the tip of the nozzle that ejects the film-forming composition and the skin: 80 mm ·Applicable environment: 20℃, 40%RH Applied voltage: 10kV

[0069] (4) Foundation application process Foundation was applied to the area where the cosmetic and electrostatic spray had been applied. Dermablend Leg & Body Makeup (color Deep Golden) manufactured by L'Oreal was applied with a sponge. Approximately 20 mg of the cosmetic was applied to the skin.

[0070] (5) Electrostatic spray process Using an electrostatic spray device 10 having the configuration shown in Fig. 1 and the appearance shown in Fig. 2, the coating composition was electrostatically sprayed onto the area where the cosmetic was applied. That is, the coating composition was electrostatically sprayed onto the skin where the cosmetic was applied, forming a coating made of fibers. The conditions for electrostatically spraying the coating composition were as follows: -Applicable area: outer part of human lower limb (5 x 5 cm), (Area to which the skin care cosmetic is applied) Electrostatic spray application time: 30 seconds ·Discharge speed of film-forming composition: 0.1g / min Distance between the tip of the nozzle that ejects the film-forming composition and the skin: 80 mm ·Applicable environment: 20℃, 40%RH Applied voltage: 10kV

[0071] (6) Cosmetic application process The emulsion was applied to the area where the cosmetic, electrostatic spray, and foundation had been applied. The emulsion shown in Table 5 was applied with a sponge. Approximately 60 mg of the cosmetic was applied to the skin.

[0072] (Evaluation of durability against moisture) For the coatings formed from fibers by electrostatic spraying on the skin after application of the skin care cosmetics in Examples 1 to 19 and Comparative Examples 1 to 3, the durability of the coatings against moisture was evaluated. For the evaluation, the film-forming composition was applied to the cosmetics and skin by electrostatic spraying to form a film made of fibers, after which warm water from a shower was applied for at least 2 minutes, the wet water was dried with a towel, and then the cosmetics shown in Table 5 were applied and used continuously until the next day, and then the evaluation was performed. The evaluation results are shown in Tables 1 to 3. The evaluation criteria were as follows. A: The cosmetic film does not crack or break at all. B: Small cracks or tears of less than 5 mm occur in the decorative film. C: The decorative film has cracks or tears of 5 mm or more but less than 2 cm. D: The decorative film is cracked or torn by more than 2 cm.

[0073] [Test Example 2] [Examples 1 to 19, Comparative Examples 1 to 3] (1) Cosmetic application process Prior to the electrostatic spraying process, 200 mg of the cosmetic composition shown in Table 4 was applied to the inside of a human forearm (5×5 cm) using a sponge. Approximately 50 mg of the cosmetic composition was applied to the skin. Application area: inner forearm (5 x 5 cm)

[0074] (2) Electrostatic spray application process The coating composition was electrostatically sprayed onto the area where the cosmetic had been applied, using an electrostatic spray device 10 having the configuration shown in Fig. 1 and the appearance shown in Fig. 2. That is, the coating composition was electrostatically sprayed onto the skin where the cosmetic had been applied, to form a coating made of fibers. Application area: inner part of human forearm (5 x 5 cm), (Area to which the cosmetic is applied) Electrostatic spray application time: 30 seconds ·Discharge speed of film-forming composition: 0.1g / min Distance between the tip of the nozzle that ejects the film-forming composition and the skin: 80 mm ·Applicable environment: 30℃, 60%RH Applied voltage: 10kV

[0075] (3) Evaluation of compatibility with cosmetics (Compatibility between cosmetics and the coating formed on fibers by electrostatic spray) For the coatings formed from fibers by electrostatic spray on the skin after the cosmetic preparations were applied in Examples 1 to 19 and Comparative Examples 1 to 3, the compatibility of the coatings with the cosmetic preparations listed in Table 4 was evaluated. The evaluation was performed by applying a film-forming composition to the skin immediately after application of the cosmetic by electrostatic spray, forming a film made of fibers, and visually observing the state from the time when the film was formed until the cosmetic and the film were completely blended together. The evaluation site was the inside of a human forearm. Here, the complete blending of the cosmetic and the film means that the film is colorless and transparent to the naked eye. In this evaluation, the film was not touched with the fingers unless otherwise specified. The evaluation results are shown in Tables 1 to 3. The evaluation criteria were as follows: A: The time it takes for the coating formed by the electrostatic spray to completely blend with the cosmetic is within 1 minute and 30 seconds after the coating has finished forming. B: The cosmetic and the coating do not blend completely within 1 minute 30 seconds, but can be made to blend completely by lightly pressing the coating from above with a hand. C: The skin care cosmetic and the film do not blend completely within 1 minute 30 seconds, and the film cannot be blended completely even when lightly pressed from above with a hand.

[0076] (4) Evaluation of softness after wetting and drying In Examples 1 to 13 and Comparative Examples 1 to 3, the coatings formed from fibers by electrostatic spray on the skin after application of the skin care cosmetics were evaluated in terms of softness to determine the effect of moisture on the coatings. The evaluation was carried out by applying the film-forming composition to the skin immediately after applying the skin care cosmetic composition shown in Table 4 by electrostatic spraying, forming a film made of fibers, and then applying room temperature shower water for 10 seconds, towel drying the wet water, waiting until the film dried, and then performing a sensory evaluation of softness. After evaluating the feel on the skin, the film was peeled off, pulled, and evaluated. The evaluation criteria were as shown below. A: There is no tension felt when the film is on the skin, and when you peel it off and pull it, it stretches and does not easily break. B: When applied to the skin, the film feels slightly tensile, and when peeled off and pulled, it stretches and is not likely to break. C: When the film is on the skin, it feels tensile, and when you peel it off and pull it, it doesn't stretch but breaks. D: When applied to the skin, the film feels very tensile, and when peeled off and pulled, it breaks without stretching.

[0077] (5) Evaluation of skin movement tracking For the coatings formed from fibers on the skin by electrostatic spraying in Examples 1 to 19 and Comparative Examples 1 to 3, the ability to follow the movement of the skin was evaluated. The evaluation area was a 5cm x 5cm area on the inside of a human forearm. The electrostatic spray was applied for 30 seconds, and after leaving it for 30 seconds, the palm was twisted inwards and then outwards five times. The evaluation results are shown in Tables 1 to 3. The evaluation criteria were as follows. A: The film conforms to the skin and does not cause any wrinkles. B: The film does not conform to the skin, causing small wrinkles when the palm is twisted. C: The film does not conform to the skin, and when the palm is twisted, it floats and wrinkles. D: The film does not conform to the skin, and even when the palm is returned, it remains floating and wrinkles occur.

[0078] (Elasticity Modulus) The elastic modulus of the coatings formed from fibers on the skin by electrostatic spraying in Examples 1 to 19 and Comparative Examples 1 to 3 was evaluated.

[0079] [Table 1]

[0080] [Table 2]

[0081] [Table 3]

[0082] *1) S-LEC B BM-1 (manufactured by Sekisui Chemical Co., Ltd.) *2) 99.5% ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) *3) Car Pole DL-30 (manufactured by ADEKA Corporation) *4) Polyglycol P-425 (manufactured by The Dow Chemical Company, Ltd.) *5) Car Pole DL-80 (made by ADEKA Corporation) *6) Citroflex-2 (Morimura Shoji Co., Ltd.) *7) Citroflex-A2 (Morimura Shoji Co., Ltd.) *8) Citroflex-A4 (Morimura Shoji Co., Ltd.) *9) Rheodol TW-S120V (Kao Corporation) *10) GENAPOL LA 030 (manufactured by Clariant Corporation) *11) FineNeo-EHS (manufactured by Nippon Fine Chemicals Co., Ltd.) *12) PEG-400 (manufactured by Sanyo Chemical Industries, Ltd.)

[0083] [Table 4]

[0084] [Table 5]

[0085] *13) Amphomer 28-4910 (Akzo Nobel) *14) Pemulen TR-1 (manufactured by Lubrizol) *15) Eumulgin B2 (manufactured by BASF) *16) GENAPOL LA 030 (manufactured by Clariant Corporation)

[0086] As can be seen from Tables 1 to 3, by electrostatically spraying directly onto the skin a composition containing (a) a polymer having film-forming ability, (b) one or more volatile substances selected from alcohols and ketones, and (c) a non-volatile oil having a logS value of -7 or more and less than 0, a film made of fibers is formed on the skin, and the film has a good elastic modulus and is excellent in compatibility with the skin, adhesion, ability to follow the movement of the skin, and durability against moisture. [Explanation of symbols]

[0087] 10 Electrostatic spray device 11 Low voltage power supply 12 High voltage power supply 13 Auxiliary Electrical Circuits 14 Micro Gear Pump 15 Container 16 Nozzles 17 Conduit 18 Flexible Pipes 19 Current limiting resistor 20. Cabinet

Claims

1. A film-forming composition for forming a film made of fibers directly on the skin by electrostatic spraying, comprising the following components (a), (b) and (c), wherein the mass ratio of component (a) to component (c) ((a) / (c)) is 1.5 or more and 8 or less, and the elastic modulus of the film formed from the film-forming composition is 1 x 10 4 N / m 2 or more and 7 x 10 6 N / m 2 or less. (a) polyvinyl butyral resin, (b) Volatile substances, including ethanol (c) 2% by mass or more and 30% by mass or less of one or more non-volatile oils selected from poly C3-C4 alkylene glycol, polyoxyalkylene alkyl ether, ester oil (excluding ultraviolet absorbers), silicone oil, and nonionic surfactant, the log S of which is -4 or more and less than 0

2. 2. The coating composition according to claim 1, wherein the mass ratio of the component (b) to the component (c), ((b) / (c)), is 9 or more and 22 or less.

3. 3. The coating composition according to claim 1, wherein the mass ratio of the content of the component (a) to the content of the component (b), ((a) / (b)), is 0.12 or more and 0.25 or less.

4. 4. The coating composition according to claim 1, wherein the content of component (a) is from 4% by mass to 35% by mass, and the content of component (b) is from 45% by mass to 95% by mass.

5. 5. The coating composition according to claim 1, wherein the content of component (a) is from 4% by mass to 30% by mass, and the content of component (b) is from 50% by mass to 93% by mass.

6. 6. The composition for forming a coating according to claim 1, wherein the content of component (c) is from 2% by mass to 25% by mass.

7. 7. The film-forming composition according to any one of claims 1 to 6, which is used in combination with a cosmetic that is applied to the skin by a means other than an electrostatic spray.

Citation Information

Patent Citations

  • Disposable cartridges for handheld electrostatic spray devices

    JP2003507165A

  • Method for skin treatment

    JP2006104211A

  • Method for producing coating

    JP2017078062A

  • Coating sheet production method

    JP2018108991A

  • External agent

    JP2018177724A